SIMULATION OF BREMSSTRAHLUNG RADIATION IN TUNGSTEN USING GEANT4 - Mukhammedov Umidjon; Safarov Abror (TADQIQOTLAR.UZ, 2024)
This study explores the generation of Bremsstrahlung radiation by electrons in tungsten (W) targets of varying thicknesses subjected to different energy beams using GEANT4 simulations. By systematically modifying the target thickness and electron beam energies, we examine the resultant radiation yield and spectrum. The results enhance our understanding of Bremsstrahlung processes in high-Z materials and provide valuable insights for applications such as radiation therapy, particle detectors, and material analysis.